Puerperal Complications Following Elective Cesarean Sections for Twin Pregnancies - Simões, T (2007)
OBJECTIVE: To estimate the maternal puerperal morbidity in elective and emergent cesareans in twins. STUDY DESIGN: We evaluated postpartum complications among patients who underwent elective cesarean birth for twin pregnancy. This group was compared to matched singletons and to emergent cesareans in twins. RESULTS: During the period September 1994-March 2006 there were 299 (47.4%) elective and 80 (12.7%) emergent cesarean sections in twin pregnancies, for a total of 379 (60.1%) cesarean births for both twins. Controls included 299 cases of elective cesareans in singletons. The comparison between elective and emergent cesareans and between elective cesareans in twins and in singletons found no significant differences in postpartum fever, scar infection, and postpartum hemorrhage. Venous thromboembolism occurred in two twin pregnancies, one in the elective and one in the emergent cesarean group. Postpartum hysterectomy was required in a singleton pregnancy following an elective cesarean birth. CONCLUSION: At present, no data exist to show a disadvantage for a planned cesarean birth for twins.